Comparison of Open and Close Exposure with Orthodontic Traction of Impacted Maxillary Canine in Orthodontic Treatments : Orthodontic Traction of Impacted Maxillary Canine - Amjad Bari, Muhammad; Wajdan, Nadia; Tariq, .; Kanju, Abid Hussain; Azeem Khan, Muhammad; Liaquat, Sahrish (Pakistan Journal of Health Sciences, 2025)
Labial impactions make maxillary canines the most affected permanent teeth after third molars, at one third. Orthodontic advice is often needed for impacted canines. Objective: To compare the outcomes of open and close exposure with orthodontic traction of impacted maxillary canine in orthodontic treatments. Methods: In this comparative prospective cohort study 54 patients with labial impacted maxillary canine were included in this study. Study was conducted from Jan 2023- Jun 2023. Non-consecutive sampling technique was used. 27 patients were managed with open technique in group I and 27 patients with closed eruption technique in group II. The evaluation encompassed a comparison of two surgical exposure methods (open and closed) mobility, vitality, periodontal health, amount of impaction, length of orthodontic therapy, and postoperative discomfort. Results: Compared to the close eruption approach, the postoperative recovery time for open eruption was significantly greater (P < 0.05). Patients reported comparable levels of postoperative discomfort; but, the closed eruption approach resulted in a more rapid resolution of that pain. The open eruption approach required less time during surgery on average compared to the closed eruption technique (P <0.05). In a direct correlation with the amount of impaction, the overall length of orthodontic treatment was shown to be longer for deeper levels of impaction. Both methods produced canines with comparable levels of energy and movement. Conclusions: In this study, the closed eruption approach took longer but reduced postoperative pain faster. Orthodontic therapy took longer with deeper impaction. Closed eruption surgeries improve periodontal tissues surrounding guided erupted teeth.